The princess and the pony - Beaton, Kate, 1983- (Arthur A. Levine Books, an imprint of Scholastic Inc., 2015)
Princess Pinecone would like a real war horse for her birthday, instead of which she gets a plump, cute pony--but sometimes cuteness can be a kind of weapon, especially in a fight with dodgeballs and spitballs and hairballs and squareballs.